Television Video Games in the Treatment of Amblyopia in Children Aged 4–7 Years. (1st October 2016) - Dadeya, Subhash; Dangda, Sonal
ABSTRACT: Aim: To investigate the role of television video games in childhood amblyopia treatment. Method: This prospective, randomized, interventional study included 40 patients between 4-7 years of age, with unilateral amblyopia (visual acuity in amblyopic eye between 1-0.6 LogMAR equivalents) attending the squint clinic at a tertiary eye hospital. All patients were prescribed optimal spectacle correction and occlusion therapy, i.e. full time patching according to patient's age, was initiated after six weeks.; full-time patching according to patient's age was initiated after 6 weeks. Subjects were randomly divided into two groups of 20 each. Patients in the first group, Group A (control), were prescribed patching alone. Patients in the second group, Group B (study), were made to play action video games, with the help of a commercial television set, along with patching. They attended 12 half-hour sessions each, at weekly intervals. Follow-up assessments included best corrected visual acuity (BCVA) (both distance and near) and stereoacuity measurements at 3, 6, 9, and 12 weeks. Results: The mean age of patients was 6.03 ± 1.14 years. The distance BCVA in the amblyopic eye showed a significant improvement at final follow-up (12 weeks) in both groups: from 0.84 ± 0.19 to 0.55 ± 0.21 LogMAReq in Group A and 0.89 ± 0.16 to 0.46 ± 0.22 LogMAReq in Group B. However, improvement in BCVA was significantly better in group B at all visits ( P =0.002, 12 weeks). The study group also had a significantly better outcome in terms near visual acuity improvement ( P = 0.006, 12 weeks). There was also greater stereoacuity improvement in group B, with 7 patients improving to 100 secs of arc or better. Conclusion: Video games supplemental to occlusion may be considered favorable for visual development in amblyopic children, and the study encourages further research on this subject.